2021
DOI: 10.1021/acsaem.0c02625
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Additives on the In Situ Crystallization Dynamics of Methyl Ammonium Lead Halide Perovskites

Abstract: Understanding the kinetics of the crystallization process for organometal halide perovskite formation is critical in determining the crystalline, nanoscale morphology and therefore the electronic properties of the films produced during thin film formation from solution. In this work, in situ grazing incidence small-angle X-ray scattering (GISAXS) and optical microscopy measurements are used to investigate the processes of nucleation and growth of pristine mixed halide perovskite (MAPbI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…[114] Besides Yoneda peak shift, perovskite nucleation and growth processes were also studied by Dunbar et al by fitting GISAXS data with a power-law model, demonstrating faster nucleation with the addition of HI and DIO additives. [115] The slope of the power-law scattering curves was related to the surface fractal dimension. [116] Lin et al, therefore, found that the surface roughness of perovskite films can become larger along with annealing owing to the increased surface fractal dimension, which explained the variation in resulted device performance.…”
Section: Discussionmentioning
confidence: 99%
“…[114] Besides Yoneda peak shift, perovskite nucleation and growth processes were also studied by Dunbar et al by fitting GISAXS data with a power-law model, demonstrating faster nucleation with the addition of HI and DIO additives. [115] The slope of the power-law scattering curves was related to the surface fractal dimension. [116] Lin et al, therefore, found that the surface roughness of perovskite films can become larger along with annealing owing to the increased surface fractal dimension, which explained the variation in resulted device performance.…”
Section: Discussionmentioning
confidence: 99%
“…[ 46 ] Also, depth‐dependent measurements can be done on, for example, crystallization direction and depth‐dependent crystal orientation was investigated during perovskite spin‐coating. [ 47 ] Today, typically one thin‐film deposition method is in the focus of such in situ studies, [ 48–50 ] while direct comparisons are scarce. However, such comparisons are essential to learn about fundamental differences between various deposition techniques and to accelerate knowledge transfer from the lab toward commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…The “soft” nature of perovskites is, in fact, characterized by ion conduction and ion migration [ 41 ], with the drawback of the instability of the perovskite, especially under operation conditions (light, moisture, heat) [ 42 ], as well as hysteresis in the devices due to the ion vacancies acting as charge traps [ 43 ]. Therefore, the use of additives firstly improves the crystal growth [ 44 ], and then the device performances and the long-term stability [ 45 ]. However, not all additives are able to blend with the perovskite precursors with the same good effects.…”
Section: Bulk Perovskitesmentioning
confidence: 99%